Nocturnal Hypoxia Activation of the Hedgehog Signaling Pathway Affects Pediatric Nonalcoholic Fatty Liver Disease Severity. Issue 7 (17th April 2019) - Sundaram, Shikha S.; Swiderska‐Syn, Marzena; Sokol, Ronald J.; Halbower, Ann C.; Capocelli, Kelley E.; Pan, Zhaoxing; Robbins, Kristen; Graham, Brian; Diehl, Anna Mae
Abstract : Chronic intermittent hypoxia and hedgehog (Hh) pathway dysregulation are associated with nonalcoholic fatty liver disease (NAFLD) progression. In this study, we determined the relationship between obstructive sleep apnea (OSA)/nocturnal hypoxia and Hh signaling in pediatric NAFLD. Adolescents with histologic NAFLD (n = 31) underwent polysomnogram testing, laboratory testing, and Sonic Hh (SHh), Indian hedgehog (IHh), glioblastoma‐associated oncogene 2 (Gli2), keratin 7 (K7), α‐smooth muscle actin (α‐SMA), and hypoxia‐inducible factor 1α (HIF‐1α) immunohistochemistry. Aspartate aminotransferase (AST) correlated with SHh, r = 0.64; Gli2, r = 0.4; α‐SMA, r = 0.55; and K7, r = 0.45 ( P < 0.01), as did alanine aminotransferase (ALT) (SHh, r = 0.51; Gli2, r = 0.43; α‐SMA, r = 0.51; P < 0.02). SHh correlated with NAFLD activity score ( r = 0.39), whereas IHh correlated with inflammation ( r = −0.478) and histologic grade ( r = −0.43); P < 0.03. Subjects with OSA/hypoxia had higher SHh (4.0 ± 2.9 versus 2.0 ± 1.5), Gli2 (74.2 ± 28.0 versus 55.8 ± 11.8), and α‐SMA (6.2 ± 3.3 versus 4.3 ± 1.2); compared to those without ( P < 0.03). OSA severity correlated with SHh ( r = 0.31; P = 0.09) and Gli2 ( r = 0.37; P = 0.04) as did hypoxia severity, which was associated with increasing SHh ( r = −0.53), Gli2 ( r = −0.52), α‐SMA ( r = −0.61), and K7 ( r = −0.42); P < 0.02. Prolonged O2 desaturations <90% also correlated with SHh ( r = 0.55) and Gli2 ( r = 0.61); P < 0.05. Conclusion : The Hh pathway is activated in pediatric patients with NAFLD with nocturnal hypoxia and relates to disease severity. Tissue hypoxia may allow for functional activation of HIF‐1α, with induction of genes important in epithelial‐mesenchymal transition, including SHh, and NAFLD progression. Abstract : Chronic intermittent hypoxia and dysregulation of the Hedgehog (Hh) pathway are associated with NAFLD progression. In adolescents with biopsy proven NASH and sleep apnea, the severity of their obstructive sleep apnea correlated with SHh ( r = 0.31, P = 0.09) and Gli2 positively ( r = 0.37, P = 0.04). The severity of hypoxia was also associated with increasing SHh ( r = −0.53), GLI2 ( r = −0.52), α‐SMA ( r = −0.61), and K7( r = −0.42), P < 0.02. The Hh pathway is activated in pediatric NAFLD patients with nocturnal hypoxia and relates to disease severity.